Method for preparing traditional lightweight porcelain from aluminosilicate solid waste
By using iron tailings, glass powder and fly ash to prepare traditional lightweight porcelain, the low-temperature firing process is used to solve the problems of solid waste resource utilization and resource consumption, and efficient solid waste treatment and ceramic performance improvement are achieved.
Patent Information
- Application Number
- CN202411382341.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
In the prior art, aluminosilicate solid waste needs to be sintered at high temperature and a large amount of natural mineral raw materials when preparing traditional light porcelain, resulting in resource consumption and environmental pollution, and the solid waste utilization rate is low.
Using iron tailings, glass powder and fly ash as raw materials, traditional lightweight quality is prepared by mixing, drying, grinding, sieving, adding polyvinyl alcohol binder, pressing, drying and low-temperature sintering (1030℃) processes. Porcelain, high-temperature melt bonding process to improve the strength of ceramics.
It realizes the resource utilization of solid waste, reduces the firing temperature and raw material costs, improves the porosity and flexural strength of ceramics, meets the performance requirements of traditional lightweight porcelain, and reaches 100% solid waste utilization rate.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a method for preparing traditional lightweight porcelain from aluminosilicate solid waste. Background Art
[0002] The bulk aluminosilicate solid wastes, mainly iron tailings and fly ash, are characterized by large output and complex composition. Iron tailings refer to solid wastes formed after mining or beneficiation. Every ton of iron concentrate will produce about three tons of tailings. According to statistics, the discharge of metal tailings reached 1.272 billion tons in 2019, of which iron tailings accounted for 520 million tons, accounting for 40.9%. Fly ash refers to the fine ash formed after coal is burned, and its main components include aluminosilicates. In 2020, my country's fly ash emissions were close to 800 million tons. These solid wastes are mainly preserved by damming and stockpiling, which not only occupies land resources, but also pollutes the environment. Possible dam breaches also pose a great threat to the lives and property safety of surrounding residents. Finding an effective and economical method for the resource utilization of solid waste is an issue we urgently need to solve.
[0003] Traditional lightweight porcelain is a lightweight ceramic product. After the finished product is glazed, the sound of knocking is similar to that of porcelain. It is lightweight and portable, and can be used in the preparation of cigarette filters; it has high strength, which can achieve lightweight design in the fields of aviation and automobiles; it has good insulation properties and can be used as a basic material for electronic components. At the same time, it can also be used as wall and floor materials in the field of building materials. Traditional lightweight porcelain is usually made of dolomite, clay, feldspar and quartz. Considering the large-scale consumption of natural mineral raw materials, mineral resources are decreasing. At the same time, solid wastes such as tailings and fly ash are similar in composition to these raw materials, mostly Al 2 O 3 、SiO 2 , CaO and MgO, etc. Some researchers have used bulk aluminosilicate solid waste to replace these natural mineral raw materials to prepare traditional ceramics. China's invention patent (201611150200.0) discloses a method for preparing foam ceramic insulation boards using gold tailings, using gold tailings, porcelain stone, feldspar, clay, and other materials as raw materials, the firing temperature is between 1185 and 1190 ° C, and the thermal insulation coefficient of the prepared ceramic insulation board is between 0.057 and 0.069 W / (m·K). China's invention patent (202211213743.8) discloses a method for preparing lightweight ceramic bricks using metal tailings, using iron tailings, black mud, Tengxian stone powder, potassium-sodium feldspar and talc as raw materials, and the firing temperature is between 1160 and 1180 ° C. The specific gravity of the prepared ceramic bricks is 1.31 to 1.51 g / cm 3, the flexural strength can reach 20.12~24.18MPa. China's invention patent (202011564612.5) discloses a method for preparing foamed ceramics using gold tailings as a base material. The raw materials include gold tailings, lightweight fillers, foam stabilizers, solvents, foaming agents, and reinforcing agents. The flexural strength of the prepared ceramics is not less than 7MPa, the thermal conductivity is 0.14W / (m·K), and the water absorption is between 0.15 and 0.73%. In the above patents, the formulas often require the addition of more than 20wt% of natural mineral raw materials, and the firing temperature is high, and the performance of the prepared products is average. Summary of the invention
[0004] Based on the above deficiencies in the prior art, the technical problem solved by the present invention is to provide an effective and economical method for resource utilization of solid waste, a method for preparing traditional lightweight porcelain using aluminosilicate solid waste, the method for preparing traditional lightweight porcelain using iron tailings, glass powder and fly ash as raw materials, thereby achieving effective treatment and resource utilization of solid waste, and having high economic, social and environmental benefits.
[0005] In order to solve the above technical problems, the present invention provides a method for preparing traditional lightweight porcelain from aluminosilicate solid waste, comprising the following steps:
[0006] S1, mixing the iron tailings, glass powder and fly ash by ball milling, and then drying, grinding and sieving to obtain a mixture;
[0007] S2, adding a binder to the mixture prepared in step S1, mixing and granulating, and aging the granulated powder at room temperature for 24 hours to obtain a formed ceramic powder;
[0008] S3, pouring the ceramic powder prepared in step S2 into a mold, pressing and drying to obtain a dry green embryo;
[0009] S4, placing the dried green body obtained in step S3 into a muffle furnace for firing, and cooling along with the furnace to obtain the lightweight porcelain.
[0010] As a preferred embodiment of the above technical solution, the method for preparing traditional lightweight porcelain from aluminosilicate solid waste provided by the present invention further includes some or all of the following technical features:
[0011] As an improvement of the above technical solution, the mass ratio of the iron tailings, glass powder and fly ash is: 75-85:20-12:5-3.
[0012] As an improvement of the above technical solution, in step S1, the ball milling mixing is specifically, the ball mill speed is 300-500 rpm, and the ball milling time is 12-24 hours (preferably, the ball mill speed is 500 rpm, and the ball milling time is 12 hours); the drying, grinding and sieving are specifically, drying at 100°C for 12 hours, and passing through a 60-mesh sieve after grinding.
[0013] As an improvement of the above technical solution, in step S2, the binder is a polyvinyl alcohol (PVA) solution with a mass fraction of 5 wt%; the added amount of the binder is 10 wt%.
[0014] As an improvement of the above technical solution, in step S3, the mold is a stainless steel mold.
[0015] As an improvement of the above technical solution, in step S3, the pressing pressure is 10 MPa and the holding time is 60 seconds.
[0016] As an improvement of the above technical solution, in step S3, the drying process is specifically to place the pressed green body into an electric heated blast drying oven and dry it at 100° C. for 24 hours until the green body reaches a constant weight.
[0017] As an improvement of the above technical solution, in step S4, the firing conditions are as follows: a heating rate of 3°C / min, a firing temperature of 1030°C, and a maximum temperature holding time of 0.5 hours.
[0018] The present invention also provides a traditional lightweight porcelain prepared from aluminosilicate solid waste, wherein the lightweight porcelain is prepared by any of the above methods.
[0019] As an improvement of the above technical solution, the lightweight porcelain has a low firing temperature (<1100°C) and a low density (<2.5g / cm 3 ), high porosity (28% ~ 35%), and high flexural strength (25 ~ 40MPa).
[0020] In this invention, in order to solve the problem of large fluctuations in the composition of iron tailings and low utilization rate, iron tailings are used as the main raw material to prepare lightweight porcelain. Through the analysis of iron tailings and auxiliary raw materials, it is determined that iron tailings are used as "aggregates", glass powder is used as high-temperature binder, and fly ash is used as reinforcing agent. A high-temperature molten bonding process is used to prepare iron tailings-based lightweight porcelain. The mechanical strength of ceramics mainly comes from the bonding of the glass phase. The strength of the glass phase has a great influence on the overall strength of the ceramic. The Al content of fly ash is 2 O 3 A high content can change the Al content in the glass phase. 3+ The coordination mode of the nanostructured carbon atoms affects the network structure of the glass phase.
[0021] This patent provides a method for preparing traditional lightweight porcelain using iron tailings, waste glass powder and fly ash as raw materials. The prepared traditional lightweight porcelain has a low firing temperature (~1030°C), the porosity of the lightweight porcelain can reach more than 25%, and the flexural strength can reach more than 30MPa, which meets the performance requirements of traditional lightweight porcelain.
[0022] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0023] (1) The traditional lightweight porcelain in the present invention is prepared by using iron tailings, glass powder and fly ash, without adding other ceramic raw materials, the raw materials are cheap, the preparation process is simple, and the solid waste utilization rate reaches 100%, which provides a new idea for the resource utilization of solid waste.
[0024] (2) The prepared traditional lightweight porcelain has high porosity and excellent flexural strength, meeting the performance requirements of traditional lightweight porcelain.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the following is a detailed description in combination with the preferred embodiments. DETAILED DESCRIPTION
[0026] The specific implementation modes of the present invention are described in detail below, which is a part of this specification. The principles of the present invention are explained through examples. Other aspects, features and advantages of the present invention will become clear through the detailed description.
[0027] The present invention uses gold tailings to prepare traditional lightweight porcelain. The materials used in the embodiment are: (1) polyvinyl alcohol: model polyvinyl alcohol 1750±50, CAS number 9002-89-5, national medicine number 30153160; (2) iron tailings: Daye, Hubei. (3) glass powder: Lingshou, Hebei. (4) fly ash: Shuozhou, Shanxi.
[0028] Example 1
[0029] (1) According to the weight ratio: 75 parts of iron ore tailings, 20 parts of glass powder, and 5 parts of fly ash are weighed.
[0030] (2) The weighed raw materials, water and agate balls are placed in a ball milling jar at a weight ratio of 1:1.5:2, and then loaded into a ball mill. The ball mill speed is 300-500 rpm, and the ball milling time is 12-24 hours to mix the raw materials evenly. The mixture is then placed in an oven at 100°C and dried for 12 hours, and then passed through a 60-mesh sieve after grinding.
[0031] (3) 10 wt % of a polyvinyl alcohol (PVA) solution with a mass fraction of 5 wt % is added to the mixture as a molding binder, and the mixture is fully mixed and granulated. The granulated powder is aged at room temperature for 24 hours to obtain a ceramic powder with excellent molding properties.
[0032] (4) Pour the granulated and aged powder into a stainless steel mold and press it at a pressure of 10 MPa for 60 seconds. Place the green body in an electric hot air drying oven and dry it at 100°C for 24 hours until the green body reaches a constant weight.
[0033] (5) The pressed green body was placed in a muffle furnace for firing at a heating rate of 3°C / min, a firing temperature of 1030°C, and a maximum temperature holding time of 0.5 hours. The sample was cooled in the furnace after firing. The main mineral phases of the prepared ceramic material are quartz, plagioclase and pyroxene. The apparent porosity is 26.50% and the density is 1.86 g / cm 3 , the flexural strength is 38.87MPa.
[0034] Example 2
[0035] (1) According to the weight ratio: 80 parts of iron ore tailings, 16 parts of glass powder, and 4 parts of fly ash are weighed.
[0036] (2) The weighed raw materials, water and agate balls are placed in a ball milling jar at a weight ratio of 1:1.5:2, and then loaded into a ball mill. The ball mill speed is 300-500 rpm, and the ball milling time is 12-24 hours to mix the raw materials evenly. The mixture is then placed in an oven at 100°C and dried for 12 hours, and then passed through a 60-mesh sieve after grinding.
[0037] (3) 10 wt % of a polyvinyl alcohol (PVA) solution with a mass fraction of 5 wt % is added to the mixture as a molding binder, and the mixture is fully mixed and granulated. The granulated powder is aged at room temperature for 24 hours to obtain a ceramic powder with excellent molding properties.
[0038] (4) Pour the granulated and aged powder into a stainless steel mold and press it at a pressure of 10 MPa for 60 seconds. Place the green body in an electric hot air drying oven and dry it at 100°C for 24 hours until the green body reaches a constant weight.
[0039] (5) The pressed green body was placed in a muffle furnace for firing at a heating rate of 3°C / min, a firing temperature of 1030°C, and a maximum temperature holding time of 0.5 hours. After firing, the sample was cooled in the furnace. The main mineral phases of the prepared ceramic material are quartz, plagioclase and pyroxene. The apparent porosity is 28.24% and the density is 1.84 g / cm 3 , the flexural strength is 31.43MPa.
[0040] Example 3
[0041] (1) According to the weight ratio: 85 parts of iron ore tailings, 12 parts of glass powder, and 3 parts of fly ash are weighed.
[0042] (2) The weighed raw materials, water and agate balls are placed in a ball milling jar at a weight ratio of 1:1.5:2, and then loaded into a ball mill at a speed of 300 to 500 rpm for 12 to 24 hours to mix the raw materials evenly. The mixture is then placed in an oven at 100°C and dried for 12 hours, and then passed through a 60-mesh sieve after grinding.
[0043] (3) 10 wt % of a polyvinyl alcohol (PVA) solution with a mass fraction of 5 wt % is added to the mixture as a molding binder, and the mixture is fully mixed and granulated. The granulated powder is aged at room temperature for 24 hours to obtain a ceramic powder with excellent molding properties.
[0044] (4) Pour the granulated and aged powder into a stainless steel mold and press it at a pressure of 10 MPa for 60 seconds. Place the green body in an electric hot air drying oven and dry it at 100°C for 24 hours until the green body reaches a constant weight.
[0045] (5) The pressed green body was placed in a muffle furnace for firing at a heating rate of 3°C / min, a firing temperature of 1030°C, and a maximum temperature holding time of 0.5 hours. The sample was cooled in the furnace after firing. The main mineral phases of the prepared ceramic material are quartz, plagioclase and pyroxene. The apparent porosity is 29.66% and the density is 1.79 g / cm 3 , the flexural strength is 32.23MPa.
[0046] The raw materials listed in the present invention, as well as the upper and lower limits and interval values of the raw materials of the present invention, and the upper and lower limits and interval values of the process parameters (such as temperature, time, etc.) can all realize the present invention, and the embodiments are not listed one by one here.
[0047] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.
Claims
1. A method for preparing traditional lightweight porcelain from aluminosilicate solid waste, characterized in that: The following steps are included: S1, mixing the iron tailings, glass powder and fly ash by ball milling, and then drying, grinding and sieving to obtain a mixture; S2, adding a binder to the mixture prepared in step S1, mixing and granulating, and aging the granulated powder at room temperature for 24 hours to obtain a formed ceramic powder; S3, pouring the ceramic powder prepared in step S2 into a mold, pressing and drying to obtain a dry green embryo; S4, placing the dried green body obtained in step S3 into a muffle furnace for firing, and cooling along with the furnace to obtain the lightweight porcelain.
2. The method for preparing traditional lightweight porcelain from aluminosilicate solid waste according to claim 1, characterized in that: The mass ratio of the iron tailings, glass powder and fly ash is 75-85:20-12:5-3.
3. The method for preparing traditional lightweight porcelain from aluminosilicate solid waste according to claim 1, characterized in that: In the step S1, the ball milling and mixing are specifically performed at a speed of 300 to 500 revolutions per minute for a ball milling time of 12 to 24 hours; the drying, grinding and sieving are specifically performed at 100° C. for 12 hours and sieving through a 60-mesh sieve after grinding.
4. The method for preparing traditional lightweight porcelain from aluminosilicate solid waste according to claim 1, characterized in that: In the step S2, the binder is a polyvinyl alcohol (PVA) solution with a mass fraction of 5 wt%; the added amount of the binder is 10 wt%.
5. The method for preparing traditional lightweight porcelain from aluminosilicate solid waste according to claim 1, characterized in that: In step S3, the mold is a stainless steel mold.
6. The method for preparing traditional lightweight porcelain from aluminosilicate solid waste according to claim 1, characterized in that: In step S3, the pressing pressure is 10 MPa and the holding time is 60 seconds.
7. The method for preparing traditional lightweight porcelain from aluminosilicate solid waste according to claim 1, characterized in that: In step S3, the drying process is specifically to place the pressed green body into an electric hot air drying oven and dry it at 100° C. for 24 hours until the green body reaches a constant weight.
8. The method for preparing traditional lightweight porcelain from aluminosilicate solid waste according to claim 1, characterized in that: In step S4, the firing conditions are as follows: a heating rate of 3°C / min, a firing temperature of 1030°C, and a maximum temperature holding time of 0.5 hours.
9. A traditional lightweight porcelain prepared from aluminosilicate solid waste, characterized by: The lightweight porcelain is prepared by the method described in any one of claims 1-8.
10. The traditional lightweight porcelain prepared from aluminosilicate solid waste as claimed in claim 9, characterized in that: The firing temperature of the lightweight porcelain is less than 1100°C and the density is less than 2.5g / cm 3 , porosity 28% ~ 35%, flexural strength 25 ~ 40MPa.
Citation Information
Patent Citations
Iron tailing sintered brick and preparation method thereof
CN112159205A
Preparation raw material, preparation method and application of multipurpose open-cell foamed ceramic
CN112341152A
Lightweight ceramic tile prepared from metal tailings and preparation method thereof
CN115572176A
All-solid waste foamed ceramic thermal insulation material and preparation method thereof
CN118373665A
Production of artificial lightweight aggregate and artificial lightweight aggregate obtained by the method
JP2000119050A
